Leaders' Cultural Responsiveness in a Rural Program Serving Latinx Youth. Issue 3 (May 2020) - McGovern, Gina; Raffaelli, Marcela; Moreno Garcia, Crystal; Larson, Reed
To provide examples of culturally responsive practices used by leaders of a rural Latinx-serving youth program, this case study focused on a community youth program in a small, rural Midwestern town. Program leaders (one White man and one Latinx woman) were both middle-aged and had postsecondary degrees. Nine Latinx youth participants (four girls, five boys; M age = 15.5 years) were primarily from Mexican immigrant families. Repeated semi-structured interviews were conducted with leaders and youth. Holistic analyses used grounded theory practices and focused on a subset of questions about cultural program experiences. Leaders of Unified Youth supported the positive development of rural Latinx youth through four categories of culturally responsive practices. They cultivated a safe space that affirmed youth's cultural values and bilingualism; served as trusted allies for youth, connecting across shared experiences and helping youth process discrimination; promoted cultural awareness and appreciation while encouraging youth to explore cultural nuances; and supported youth's leadership development and advocacy through community events promoting cultural awareness. These rich descriptions of practices contribute to our understanding of cultural responsiveness in context and can be used to inform research, policy, and practice with Latinx youth in rural communities.